2010
DOI: 10.1021/ie100375b
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric Hollow-Fiber Heat Exchangers for Thermal Desalination Processes

Abstract: Metallic shell-and-tube heat exchangers used in thermal desalination require huge capital investments, suffer from corrosion/erosion, create heavy metal pollution, and display a large footprint. This paper has explored their potential replacement by polymeric solid hollow fiber-based heat exchangers. Using solid hollow-fibers of polypropylene (PP) (wall thickness 75 µm, outside diameter 575 µm) a number of heat exchangers were fabricated in the laboratory (heat exchange area, 195-960 cm 2 ) and at a commercial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 7 publications
(18 reference statements)
1
31
0
Order By: Relevance
“…Song et al 53 proposed experiments and numerical simulation of solid polymeric hollow fibres heat exchangers (PHFHE) for thermal desalination process. Three types of polymeric hollow fibres (as shown in Figure 21) including solid PP, solid PEEK and asymmetric polyethersulfone (PES) with nonporous coatings were used to produce the heat exchangers.…”
Section: Polymer Micro-hollow Fibre Heat Exchangermentioning
confidence: 99%
“…Song et al 53 proposed experiments and numerical simulation of solid polymeric hollow fibres heat exchangers (PHFHE) for thermal desalination process. Three types of polymeric hollow fibres (as shown in Figure 21) including solid PP, solid PEEK and asymmetric polyethersulfone (PES) with nonporous coatings were used to produce the heat exchangers.…”
Section: Polymer Micro-hollow Fibre Heat Exchangermentioning
confidence: 99%
“…The shell had two additional openings; one was connected (not shown) to a liquid absorbent reservoir kept mildly pressurized to prevent gas bubbling in the absorbent from the gas passing through the bore of the porous hollow fibers. We could have used inexpensive solid polypropylene hollow fibers [21,22] since as we will see later the stripping temperature employed here did not exceed 95-97 o C.…”
Section: Equilibrium Absorption Characterizationmentioning
confidence: 99%
“…Otherwise the equilibration time is long. The polymeric solid PEEK hollow fibers having a thin wall transfer heat with great efficiency [21,22] and can rapidly heat the absorbent in the inter-fiber space if we introduce hot water or low temperature steam through their lumen. These solid hollow fibers can also absorb the exothermic heat of absorption during CO 2 absorption if cold water is passed through their lumen for isothermal absorption.…”
Section: Equilibrium Absorption Characterizationmentioning
confidence: 99%
“…It was shown that the overall conductance per unit of volume of the PHFHE (around 1.2 · 10 6 W/m 3 K) is larger than in the case of conventional metallic shell-and--tube exchangers and slightly less than in the case of the plate heat exchangers. Song et al (2010) presented a lab study aimed at the use PHFHEs in the thermal desalination process. The metallic heat exchangers suffer from corrosive behaviour of salt water while the plastics withstand salt water quite well.…”
Section: Introductionmentioning
confidence: 99%